2012
DOI: 10.2355/isijinternational.52.464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Parameters on Microstructures and Mechanical Properties of a Nano/ultrafine Grained Low Carbon Steel Produced by Martensite Treatment Using Plane Strain Compression

Abstract: In this work, the martensite treatment consisting of cold deformation by plane strain compression and subsequent annealing was used for producing the nano/ultrafine grained structure in a low carbon steel. The equivalent strain was varied from 0.1 to 2, while the annealing process was carried out in the temperature range of 400-600°C for 0-180 min. The microstructural evolution and mechanical properties of the as-deformed and annealed specimens were investigated. The results showed that in the as-deformed spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Cold rolling of such ultrafine microstructure enhanced the dislocation density and the beginning martensite fragmentation. As reported by Ghasemali et al 10) , more than 65% reduction in thickness was required for martensite fragmentation and Hosseini et al 14) proved that increasing cold deformation to 85% reduction in thickness led to achieving finer ferrite grains. Figure 3 reveals SEM image of 85% cold rolled martensite in Nb .04 sample, which was composed of fully lamellar dislocation cells (LDCs).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Cold rolling of such ultrafine microstructure enhanced the dislocation density and the beginning martensite fragmentation. As reported by Ghasemali et al 10) , more than 65% reduction in thickness was required for martensite fragmentation and Hosseini et al 14) proved that increasing cold deformation to 85% reduction in thickness led to achieving finer ferrite grains. Figure 3 reveals SEM image of 85% cold rolled martensite in Nb .04 sample, which was composed of fully lamellar dislocation cells (LDCs).…”
Section: Resultsmentioning
confidence: 82%
“…Figure 5 reveals SEM microstructure of 85% cold rolled samples after warm temperature annealing at 550 ºC for 300 s. Annealing of deformed Nb .00 sample in such circumstances led to the complete formation of ferrite with mean grain size of 87 nm, but there were some grains bigger than others (Figure 5(a)). This phenomenon had been reported by Hoseini et al 14) and it is called "abnormal grain growth". The reason for this occurrence is minimizing the role of cementite carbide in the prevention of grain boundaries migration at higher temperatures.…”
Section: Fig 3 Sem Image Of 85% Cold Rolled Martensitementioning
confidence: 69%
See 1 more Smart Citation
“…Some research has been conducted on the development of thermomechanical processes for the production of ultrafine grain low carbon steels. Martensite treatment including cold deformation by plane strain compression followed by annealing has been used to produce nano/ultrafine grain low carbon steel [8]. It was reported that 91% cold rolling of dual phase starting microstructure including ferrite and martensite, and subsequent annealing below the eutectoid temperature, resulted in the production of ultrafine grain structure in low carbon steel [9].…”
Section: Introductionmentioning
confidence: 99%